The FINANCIAL PERFORMANCE ANALYSIS TO MEASURE THE COOPERATIVE HEALTH OF PTN BLU IN PALEMBANG CITY - Harson Harson; Isni Andriana; Mohamad Adam (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2022)
This study aimed to determine and analyze the financial performance of cooperatives at Public Service Agency State Universities (PTN BLU) Palembang City. Data were analyzed using financial ratios, as a population of Civil Servant Cooperatives PTN BLU Palembang City and samples of financial reports for 2010 -2021, the results of the study show that the liquidity ratio, capital ratio, profitability ratio for the Sriwijaya University cooperative are in good health with the values of the three ratios above the established average, while for the Raden Fatah Palembang State Islamic University cooperative only the profitability ratio is in an unhealthy state. For liquidity and capital ratios in a healthy state of results, the assessment of the results of this ratio is based on the Regulation of the Minister of Cooperatives and UKM number 06/Dep.6.1V/2016 concerning guidelines for evaluating savings and loan cooperatives and cooperative saving and loan units. The results of this study are expected to be a reference and input for further researchers and institutions where research is conducted in improving financial performance management so that the established rules obtain good criteria.